2016
DOI: 10.1089/dia.2016.0010
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Heart Rate Variability Measures and Blood Glucose Levels: Implications for Noninvasive Glucose Monitoring for Diabetes

Abstract: This study demonstrates links between specific HRV variables and BGL. In the future the dynamic nature of HRV could provide a unique and real-time method for monitoring BGL, for continuous noninvasive prediction and/or management of DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 55 publications
3
21
1
1
Order By: Relevance
“…Previous report described delayed HRR and abnormal HRV in DM patients [2,19]. Reduced HRR reflected impaired vagal functional status after exercise [23].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous report described delayed HRR and abnormal HRV in DM patients [2,19]. Reduced HRR reflected impaired vagal functional status after exercise [23].…”
Section: Discussionmentioning
confidence: 86%
“…Hypoglycemic therapy is the main approach for the prevention of organ complications in DM patients, and glycosylated hemoglobin (HbA1c) level is a common parameter measured in the clinical practice, which reflects the status of blood glucose levels in recent 3 months [18] and is also an important monitoring parameter of hypoglycemic therapy. Previous studies indicated that HRR or HRV parameters were significantly correlated with blood glucose level in DM patients [4,19]. However, reports on the association between HbA1c level and HRR or HRV parameters in DM patients are scanty.…”
Section: Introductionmentioning
confidence: 98%
“…Higher HRV is associated with greater capacity for emotion regulation (Appelhans & Luecken, ; Mather & Thayer, ), metacognitive awareness and mind reading (Lischke, Lemke, Neubert, Hamm, & Lotze, ; Meessen, Sütterlin, Gauggel, & Forkmann, ), empathy and alexithymia (Lischke et al ., ), and with greater performance on several cognitive tasks involving attention, working memory, and inhibitory control (Hansen, Johnsen, & Thayer, , ; Ottaviani et al ., ; Saus et al ., ). Relevantly, higher vagal tone has also been associated with better physical health: better glucose regulation, better HPA axis function, reduced inflammation, reduced risk for cardiovascular disease, and all‐cause mortality (Hillebrand et al ., ; Rothberg, Lees, Clifton‐Bligh, & Lal, ; Thayer & Fischer, ; Thayer, Yamamoto, & Brosschot, ).…”
Section: The Vagus Nerve and The Neurovisceral Integration Modelmentioning
confidence: 99%
“…Moreover, there is no consensus on the decreased levels of HRV parameters in T2DM. Furthermore, despite HRV being linked with the severity of T2DM [ 23 ], no studies have comprehensively assessed the role of the most common variables, such as age [ 24 ], gender [ 25 ], blood glucose control [ 26 ], or medications treating for T2DM, on HRV parameters [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%